DETERMINATION OF INLET AIR FLOW RATE IN GAS TURNINES - Pusat, Saban; Akkoyunlu, Mustafa Tahir; Erdem, Hasan Huseyin (YILDIZ TECHNICAL UNIV, 2014)
Performance of gas turbines, which have been used commonly in electricity production and cogeneration systems, affect cost of electricity considerably. However, for determination and recovery of performance losses and for doing planned maintenance, lots of measurements and analyses are required. As in all turbo machineries, one of these measurements is flow rate of process fluid. Aim of this study is to give a method to calculate compressor inlet air mass flow that is difficult to measure and has low reliability for gas turbines. The calculation method mainly based on combustion equation and measured data taken from flue gas emission device. Basic inputs of the method are fuel content, fuel mass flow, relative humidity, temperature and pressure of ambient air and oxygen content and pressure of flue gas. By using this method for gas turbines, compressor inlet air mass flow can be calculated practically. By this means, it is possible to determine and follow the performance of compressor and gas turbine correctly by operators.
Keywords: Gas turbine; compressor inlet air flow; oxygen rate; fuel content; Engineering